Effects of protein-calorie restriction on mechanical function of hypertrophied cardiac muscle - Cicogna, Antonio Carlos [UNESP]; Padovani, Carlos Roberto [UNESP]; Georgette, José Carlos [UNESP]; Aragon, Flávio Ferrari [UNESP]; Okoshi, Marina Politi [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 1999)
OBJECTIVE: To assess the effect of food restriction (FR) on hypertrophied cardiac muscle in spontaneously hypertensive rats (SHR). METHODS: Isolated papillary muscle preparations of the left ventricle (LV) of 60-day-old SHR and of normotensive Wistar-Kyoto (WKY) rats were studied. The rats were fed either an unrestricted diet or FR diet (50% of the intake of the control diet) for 30 days. The mechanical function of the muscles was evaluated through monitoring isometric and isotonic contractions. RESULTS: FR caused: 1) reduction in the body weight and LV weight of SHR and WKY rats; 2) increase in the time to peak shortening and the time to peak developed tension (DT) in the hypertrophied myocardium of the SHR; 3) diverging changes in the mechanical function of the normal cardiac muscles of WKY rats with reduction in maximum velocity of isotonic shortening and of the time for DT to decrease 50% of its maximum value, and increase of the resting tension and of the rate of tension decline. CONCLUSION: Short-term FR causes prolongation of the contraction time of hypertrophied muscles and paradoxal changes in mechanical performance of normal cardiac fibers, with worsening of the shortening indices and of the resting tension, and improvement of the isometric relaxation.
Keywords: food restriction; myocardial function; spontaneously hypertensive rat